2020
DOI: 10.1161/strokeaha.119.027740
|View full text |Cite
|
Sign up to set email alerts
|

Prestroke Disability Predicts Adverse Poststroke Outcome

Abstract: Objectives: Information concerning pre-stroke disability on stroke outcomes is lacking. We assessed pre-stroke disability in relation to post-stroke outcomes whilst in hospital. Design: Analysis of prospectively collected data from the Sentinel Stroke National Audit Programme (SSNAP). Setting: Four major UK hyperacute stroke units (HASUs) between 2014 and 2016. Participants: 1656 men (mean age ±SD=73.1yrs ±13.2) and 1653 women (79.3yrs ±13.0) admitted with acute stroke. Main outcome measures: Pre-stroke disabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…Appropriate adjustments were made including age, sex and presenting diagnoses. Characteristics of this study have been shown to be similar to those of the UK population [12,33,34]. There are certain limitations in the present study that may arise from patients who have left our catchment area or those who were readmitted to other centres this would lead to an underestimation of Fig.…”
Section: Discussionmentioning
confidence: 71%
“…Appropriate adjustments were made including age, sex and presenting diagnoses. Characteristics of this study have been shown to be similar to those of the UK population [12,33,34]. There are certain limitations in the present study that may arise from patients who have left our catchment area or those who were readmitted to other centres this would lead to an underestimation of Fig.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, as strokes tend to reoccur in the same patient, even in cases of acute stroke, the chronic lesion segmentation models can aid in foreseeing the prognosis. Chronic stroke segmentation can predict the pre-stroke modified rankin score (pre-mRS) [30], which is an independent predictor of poststroke prognosis [31]. This highlights the role of chronic stroke segmentation models in both acute and chronic stroke settings.…”
Section: Limitationsmentioning
confidence: 89%
“…Furthermore, as strokes tend to reoccur in the same patient, even in cases of acute stroke, the chronic lesion segmentation models can aid in foreseeing the prognosis. Chronic stroke segmentation can predict the pre-stroke modified Rankin score (pre-mRS) [ 34 ], which is an independent predictor of poststroke prognosis [ 35 ]. This highlights the role of chronic stroke segmentation models in both acute and chronic stroke settings.…”
Section: Discussionmentioning
confidence: 99%